Sodobna družina in družinska medicina kot vir pomoči - Pesjak, Katja (Medicinski razgledi, 2006)
Never in the past have parents paid so much attention to their children as they do today. The fundamental issue is socialization of children, with which parents try to give them the best possible chances of success in society. Postmodern family is characterized by rapid changes the environment provides endless opportunities from which children and young people must choose. This creates complex personalities and the profession of family practice is also aware of the importance of a holistic approach in medicine. In their treatmentstrategies, family practitioners include all three dimensions - the biological, psychological and social dimension. Emergence of diseases and their treatment are related to each of these three areas.
Keywords: Družina, značilnosti; Family Practice; Družinska medicina; Family Characteristics; Family Leave; Družinski, bolniški dopust; Parent-Child Relations; Starši-otrok, odnosi; family; družina; child; otroci; zdravstveno varstvo